RELATIONSHIP BETWEEN MOTHER’S EDUCATION AND EMPLOYMENT STATUS WITH COMPLEX FEEDING IN WORK AREA OF PUSKESMAS SUAK RIBEE WEST ACEH DISTRICT - Tiara, Anita; Pane, Mustika Dewi (Juru Rawat. Jurnal Update Keperawatan, 2025)
Inappropriate complementary feeding can cause malnutrition in children. Malnutrition will cause a weak immune system so that children will often get sick. This is one of the main problems worldwide, especially in developing countries. This study aims to determine the relationship between education and employment status with the provision of complementary feeding in the Suak Ribee Health Center Work Area, West Aceh Regency. The research design used cross-sectional. The population in this study were mothers who had babies aged 0-6 months as many as 167 people using the total sampling technique. The instruments used were questionnaires and analyzed using univariate and bivariate analysis with the chi-square test. The results of the statistical test obtained maternal education with a p value of 0.001 and maternal employment status with a p value of 0.004. The conclusion was that there was a relationship between maternal education and employment status with the provision of complementary feeding (MP-ASI) in the Suak Ribee Health Center Work Area, West Aceh Regency.It is hoped that health workers in the Suak Ribee Health Center Work Area can create programs or health education about appropriate complementary foods for babies